Extraction and evaluation of condensed tannins from bark of eleven species of trees from Costa Rica - Aguilar-López, Jorge (2012)
The chemical nature of condensed tannins offers a natural source of such organic compounds, with potential application to medicinal and industrial uses. The extraction and analysis of this type of metabo- lites from plants of many regions of the world have been the objective of researching groups. In this case, it is desired to contribute to present knowledge, establishing the nature and amounts of condensed tannins extracted from bark of 11 tree species grown in Costa Rica: guanacas- te (Enterolobium cyclocarpum), alcornoque (Licania arborea), jobo (Spondias mombin), pochote (Pachira quinata), níspero (Manilkara chicle), almendro (Andira inermis), roble (Tabebuia rosea), cedro (Cedrela odo- rata), cenízaro (Samanea saman), pino (Pinus cari- baea) and ciprés (Cupressus lusitanica). Bark samples of all mentioned species were pre- pared, dried and extracted with ethanol. Ethanolic extracts were analyzed to determine the condensed tannins content by Stiasny number and characteri- zed by infrared spectroscopy (FT-IR). The species with higher proportion of extracted material were guanacaste (9.5841% w/w), pochote (15.0066% w/w), pino (19.3400% w/w) and ciprés (10.5300% w/w), meanwhile extracts with higher proportions of condensed tannins were the obtai- ned from alcornoque (61.9%), jobo (66.1%), pocho- te (72.8%), níspero (50.5%), cedro (72.7%) and pino (70.7%).